Introduction to modern economic growth / Daron Acemoglu. - Acemoglu, Daron (Princeton University Press, 2009)
Daron Acemoglu gives graduate students not only the tools to analyze growth & related macroeconomic problems, but also the broad perspective necessary to apply those tools to the big-picture questions of growth & divergence. He also introduces the economic & mathematical foundations of modern growth theory & macroeconomics.